Case report: Hepatectomy with Rex bypass for a child with hepatoblastoma and portal vein thrombosis - Kitagawa, Norihiko; Shinkai, Masato; Asano, Fumio; Tsuzuki, Yukihiro; Mochizuki, Kyoko; Usui, Hidehito; Yagi, Yuma; Kawami, Akio; Okumura, Kazuyoshi; Yokosuka, Tomoko; Goto, Hiroaki; Nozawa, Kumiko; et al. (Frontiers in Pediatrics, 2023)
Pediatric liver tumors with portal vein obstruction are often candidates for liver transplantation. However, lifelong use of immunosuppressants and invasiveness to healthy donors in the case of living-donor liver transplantation is inevitable. Moreover, when lung metastasis is involved, the lung recurrence rate after liver transplantation is still high. Therefore, transplantation should be avoided as much as possible. In cases of tumor in the right lobe of the liver, complete resection of the portal vein trunk may be possible by creating a Rex bypass, but with the original method, end-to-side anastomosis to the umbilical portal vein is difficult in small children. We report a case of a 2-year-old girl with hepatoblastoma in whom a Rex shunt was created by end-to-end anastomosing the recanalized umbilical vein to the portal vein stump with interposing a vein graft, and the right lobe was successfully resected along with the tumor.